Identifikasi Risiko Rantai Pasok dengan Metode House of Risk (HOR) - Juniardo Akmal Hadi; Melinska Ayu Febrianti; Gisya Amanda Yudhistira; Qurtubi Qurtubi (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
Modern era has an impact on the manufacturing industry. Relate to technology to turn raw goods into finished goods. Look at competitive in competition between companies that are required to customer demand. PT XYZ is a textile company. The dynamic demand for fabrics has the impact of abundant inventory and uncertain raw material delivery waiting times make it difficult for the company to meet all demand. Risk identification using Failure Mode and Effect Analysis (FMEA) method, assessing the importance of the effectiveness business processes in the risk implications that occur. Then, the House of Risk (HOR) approach can be analyzed against potential risks in the company when conducting production and look at the degree of probability risk as well as the impact that occurs and impacts decision making so as not to be detrimental. The results of this study show that there are 5 risk events and 28 risk agents that become supply chain risks as well as recommendations to the priority risk agents